POLA BELAJAR DARING ANAK DI TEMP AT PEKERJAAN ORANG TUA PADA PERUMAHAN GRIYA FIRDAUS PERMAI KELURAHAN TUAHMADANI KECAMATAN TUAH MADANI KOTA PEKANBARU - Amelia, Sisi; Achmad, Said Suhil; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the online learning patterns of children in theparents' workplace at the Griya Firdaus Indah housing estate, Tuahmadani sub-district,Tuah Madani sub-district, Pekanbaru City and the learning pattern itself consists ofindependent learning, group learning, discussion learning and peer tutoring. Thepurpose of this study is to describe the pattern of children's learning processes duringonline learning at the parents' workplace at Griya Firdaus Permai Housing,Tuahmadani Village, Tuah Madani District, Pekanbaru City. The type of research usedin this study is descriptive with a qualitative approach, aiming to describe the behaviorunder study. The data collection process was carried out by interviewing 6 researchinformants consisting of 3 core informants and 3 control informants supported bydocumentation. Based on the results of interviews with research informants, byinterviewing 6 informants with the same opinion, the researcher found 3 existinglearning patterns used by children studying at their parents' workplace, namelycollaborative learning patterns, discussion learning patterns and peer tutor learningpatterns. The study of learning patterns is very well applied to children who study at theworkplace of their parents, this is done so that children have good learning patternsand will make children's learning activities run well even though the child is in theparent's work environment.Key Words: Children's Learning Pattern